CHOICE OF FORUM DALAM PENYELESAIAN SENGKETA PERBANKAN SYARIAH PASCA TERBITNYA PUTUSAN MAHKAMAH KONSTITUSI NO.93/PUU-X/2012 - Yunari, Afrik (Ahkam: Jurnal Hukum Islam, 2016)
The dispute resolution process which emerges after the issue of the Islamic Banking Law No. 21/2008, has led to occurrence of dispute settlement or contention regarding to the institution for the dispute resolution. The dispute occurs between the Basyarnas with the District Court or between Basyarnas with Religious Courts or between the Religious Courts with the District Court. This problem occurs due to legal clarification of Article 55, Paragraph 2 issued by the Constitution Court, which confirms that the article is against the Constitution and has no binding legal force. This study discusses the possible alternative of dispute settlement forum in Islamic banking after the publication of the legal decision of the Constitution Court No. 93/PUU-X/2012, discuss the sharia banking dispute resolution before and after the inception of Act No. 21/ 2008 about Islamic banking, the legal decision of the Constitution Court No. 93/PUU-X/2012, and the choice of dispute settlement forum in Islamic banking after publication of the legal decision of the Constitution Court No. 93/PUU-X/2012. Kata kunci: Choice of Forum, Sengketa Perbankan Syariah, MK No. 93/PUU-X/2012